Aging-resistant rubber material for rubber-lined pipes and preparation method thereof
By using silica/titanium dioxide/carbon nanotimal pipe composite material as a processing assistant, and combined with the soluble gel method and two sections of sulfide methods, the problem of poor anti -aging performance and weak antibacterial ability of fluorine rubber significantly improved its mechanics Power and durability.
Patent Information
- Application Number
- CN202310253964.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-03-16
AI Technical Summary
When used in rubber lining pipes, existing fluoroelastomers have problems such as poor anti-aging performance and weak antibacterial ability, which affects storage and service life.
The self -made silica/titanium dioxide/carbon nanopotorum composite material is used as a machined auxiliary, and the silicon dioxide layer is prepared on the surface of the carbon nanotubes through the soluble gel method, combined with two sections of sulfide methods to prepare fluorine rubber.
Significantly improve the mechanical strength, aging resistance and antibacterial ability of fluorine rubber, and extend the storage time and service life of fluorine rubber.
Smart Images

Figure BDA0004128868650000081 
Figure BDA0004128868650000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field, in particular to an anti-aging rubber for a rubber-lined pipe and a preparation method thereof. Background Art
[0002] Rubber-lined pipe is a pipe with a special structure, which is widely used in the fields of chemical industry, food, mineral, fertilizer, etc. Usually, the outer side of the rubber-lined pipe is steel or other hard materials as the skeleton, and the inner side is wear-resistant and corrosion-resistant rubber. Due to the unique physical and chemical properties of rubber itself, it can not only serve as a buffer layer to reduce the impact of the pipeline conveying medium on the external structure, but also isolate the conveying medium from the outer skeleton to prevent corrosion, thereby reducing the pipeline maintenance cost and extending the service life.
[0003] Rubber is a type of highly elastic polymer material with reversible deformation, which is divided into natural rubber and synthetic rubber. Natural rubber is restricted by the climate of its origin, and its output is relatively low and unstable. As one of the three major synthetic materials, synthetic rubber has many categories and is widely used. It has good air tightness, elasticity, cold resistance, heat resistance and other characteristics, involving chemical, aviation, automotive and other fields. Among them, fluororubber has good high temperature resistance, oil resistance and chemical corrosion resistance, and can effectively resist most acid, alkali, oil and other solutions. It is very suitable for use in rubber-lined pipes, but it also has problems such as poor anti-aging performance and weak antibacterial ability, which affects storage and service life. Therefore, it is necessary to develop a new method for preparing fluororubber. Summary of the invention
[0004] The object of the present invention is to provide an aging-resistant rubber material for rubber-lined pipes and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an aging-resistant rubber material for rubber-lined pipes and a preparation method thereof, comprising the following steps:
[0006] Step 1: Preparation of processing aids:
[0007] S1: First, the carbon nanotubes are sintered at 500°C for 10 hours, then placed in pure water to wash away surface impurities, acidified with 65% concentrated nitric acid for 6 hours, added to a mixed solution of ethanol and titanate compound at room temperature, heated to 50°C in a water bath, added with nitric acid, stirred for 2 hours, reacted in a water bath at 75-85°C for 8 hours, and then added with pure water to cool to room temperature to obtain a titanium dioxide / carbon nanotube solution;
[0008] S2: The silicate compound, ethanol, nitric acid and pure water are fully mixed and stirred to obtain a mixed solution A; ethanol is added to the nitric acid solution to obtain a mixed solution B, which is added to the mixed solution A, and heated in a water bath at 55-65° C. with stirring, and reacted for 3-5 hours to obtain a silica solution;
[0009] S3: The titanium dioxide / carbon nanotube solution and the silicon dioxide solution are mixed and stirred for 30 minutes, ethanol, diacetone alcohol and N,N-dimethylformamide are added and stirred for 30 minutes, and then ethanol, ethylene glycol methyl ether and N,N-dimethylformamide are added and stirred for 90 minutes to obtain a mixed solution C; the mixed solution C is dried at 100° C. to obtain a processing aid;
[0010] Step 2: Add fluororubber raw rubber, processing aid, antioxidant, plasticizer and flame retardant into an internal mixer, fully mix the materials at 150-180°C, extrude, draw and pelletize through a twin-screw extruder at 160-190°C to obtain raw rubber mixed rubber;
[0011] Step 3: Using a two-stage vulcanization method, add the vulcanizing agent and the raw rubber mixed rubber prepared in step 2 into an internal mixer and disperse them evenly, and then obtain the finished product through a hot pressing process.
[0012] In S1, the contents of the components are, by weight, 7 to 10 parts of ethanol, 3 to 5 parts of titanate compounds, 90 to 100 parts of pure water, 4 to 5 parts of nitric acid, and 5 to 10 parts of carbon nanotubes.
[0013] Furthermore, the titanate compound is any one of tetraethyl titanate, tetraisopropyl titanate, and tetra-tert-butyl titanate.
[0014] In S2, the silicon dioxide solution contains, by weight, 20 to 22 parts of mixed solution A and 2 to 4 parts of mixed solution B.
[0015] Furthermore, the contents of the components in the mixed solution A are, by weight, 6 to 8 parts of silicate compound, 15 to 20 parts of ethanol, 0.6 to 0.9 parts of nitric acid, and 0.5 to 1 parts of pure water; the contents of the components in the mixed solution B are, by weight, 0.4 to 0.5 parts of ethanol and 0.5 to 0.8 parts of nitric acid.
[0016] Furthermore, the silicate compound is any one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, isopropyl silicate, and butyl orthosilicate, preferably ethyl orthosilicate.
[0017] In S3, the contents of the processing aid components are, by weight: 25-28 parts of titanium dioxide / carbon nanotube solution, 15-20 parts of silicon dioxide solution, 4 parts of ethanol, 2 parts of diacetone alcohol, 3 parts of N,N-dimethylformamide, and 1.8 parts of ethylene glycol methyl ether.
[0018] In step 2, the contents of the components of the raw rubber compound are, by weight, 120 to 150 parts of fluororubber raw rubber, 15 to 30 parts of processing aids, 1 to 5 parts of antioxidants, 1 to 3 parts of plasticizers, and 1 to 3 parts of flame retardants.
[0019] Furthermore, the fluororubber raw rubber is any one of a copolymer of chloroethylene and trifluoroethylene, a copolymer of vinylidene fluoride and hexafluoropropylene, a copolymer of vinylidene fluoride and trifluoroethylene, and a copolymer of vinylidene fluoride and hexafluoropropylene; the antioxidant is one or more of 1010, 168, 1076, 626, and 1790; the plasticizer is one or more of dioctyl adipate, butyl epoxy oleate, dioctyl sebacate, propylene glycol adipate, polyisobutylene, and palm wax; the flame retardant is one or more of antimony trioxide, melamine cyanurate, 4-bromophenol, and pentabromodiphenyl ether.
[0020] In step 3, the content of each component, by weight, is 0.5 to 1.4 parts of vulcanizing agent and 100 to 120 parts of raw rubber mixed rubber.
[0021] Furthermore, the vulcanizing agent is any one of sulfur, benzoyl peroxide, and 2,4-dichlorobenzoyl peroxide.
[0022] Furthermore, the first stage vulcanization conditions are: pressure 9-10MPa, temperature 160-170°C, time 10-15min; the second stage vulcanization conditions are: temperature 190-210°C, time 2-4h; during the molding process, the temperature is controlled at 150-240°C, the pressure is 1-3Mpa, and the molding time is 0.5-2h.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention uses a self-made silica / titanium dioxide / carbon nanotube composite material as a processing aid for the synthesis of fluororubber to improve the mechanical strength, aging resistance and antibacterial ability of fluororubber. Carbon nanotubes have a very strong surface effect, and are prone to agglomeration when directly blended with fluororubber, resulting in uneven products, affecting the appearance and quality of use. The present invention uses a sol-gel method to prepare a layer of silica on the surface of carbon nanotubes, which can not only improve the strength of fluororubber, but also avoid agglomeration of carbon nanotubes; in addition, titanium dioxide can not only improve the strength of fluororubber and the effects of antibacterial sterilization and anti-ultraviolet aging, but also as a metal oxide can improve the heat resistance of fluororubber and extend the storage time and service life of fluororubber. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the following embodiments, the main sources of materials are as follows: carbon nanotubes are from Shenzhen Turing Evolution Technology Co., Ltd.; tetraethyl titanate is from Dofukate, CAS No.: 3087-36-3; ethyl orthosilicate is from Hangzhou Guibao Chemical Co., Ltd., CAS No.: 78-10-4; nitric acid is from Tengsheng Chemical, CAS No.: 9697-37-2; ethanol is from McLean, CAS No.: 64-17-5; diacetone alcohol is from Suzhou Pules Biotechnology Co., Ltd., CAS No.: 123-42-2; N,N-dimethylformamide is from Xinsheng Chemical, CAS No.: 68-12-2; ethylene glycol methyl ether is from Qingdao Hailijia New Materials Co., Ltd., CAS No.: 109-86-4; antioxidant 1010 is from Shanghai Lingrui Chemical Co., Ltd.; palm wax is from Shanghai Yiba Chemical Raw Materials Co., Ltd.; 4-bromophenol is from Yuanye Bio, CAS No.: 106-40-2; titanium dioxide powder is from Hubei Huifu Nanomaterials Co., Ltd.; silicon dioxide powder is from Shandong Wanhua Tianhe New Materials Co., Ltd.
[0026] Embodiment 1:
[0027] Step 1: Preparation of processing aids:
[0028] S1: First, 5 parts of carbon nanotubes were sintered at 500°C for 10 hours, then placed in pure water to wash away surface impurities, acidified with 65% concentrated nitric acid for 6 hours, added to a mixed solution of 7 parts of ethanol and 3 parts of tetraethyl titanate at room temperature, heated to 50°C in a water bath, stirred for 2 hours, added with 4 parts of nitric acid, reacted in a water bath at 75°C for 8 hours, and then added with 100 parts of pure water to cool to room temperature to obtain a titanium dioxide / carbon nanotube solution;
[0029] S2: 6 parts of tetraethyl orthosilicate, 15 parts of ethanol, 0.9 parts of nitric acid and 0.5 parts of pure water were fully mixed and stirred to obtain a mixed solution A; 0.4 parts of ethanol were added to 0.8 parts of nitric acid solution to obtain a mixed solution B; 2 parts of the mixed solution B were added to 22 parts of the mixed solution A, heated in a water bath at 55°C with stirring, and reacted for 3 hours to obtain a silicon dioxide solution;
[0030] S3: 25 parts of titanium dioxide / carbon nanotube solution and 20 parts of silicon dioxide solution were mixed and stirred for 30 minutes, and a mixed solution of 2 parts of ethanol, 2 parts of diacetone alcohol and 1 part of N,N-dimethylformamide was added and stirred for 30 minutes, and then a mixed solution of 2 parts of ethanol, 1.8 parts of ethylene glycol methyl ether and 2 parts of N,N-dimethylformamide was added and stirred for 90 minutes to obtain a mixed solution C; the mixed solution C was dried at 100° C. to obtain a processing aid;
[0031] Step 2: 120 parts of fluororubber raw rubber, 15 parts of processing aid, 1 part of antioxidant 1010, 1 part of palm wax, and 2 parts of 4-bromophenol are added to an internal mixer, the materials are fully mixed at a temperature of 150°C, and then extruded, stretched, and pelletized through a twin-screw extruder at 160°C to obtain a raw rubber compound;
[0032] Step 3: Use a two-stage vulcanization method to add 0.5 parts of 2,4-dichlorobenzoyl peroxide and 120 parts of raw rubber mixed rubber into an internal mixer and disperse them evenly, and then undergo a hot pressing process to obtain a finished product. The first-stage vulcanization conditions are: pressure 9MPa, temperature 160°C, time 10min; the second-stage vulcanization conditions are: temperature 210°C, time 2h; during the molding process, the temperature is controlled at 150°C, the pressure is 1Mpa, and the molding time is 2h.
[0033] Embodiment 2:
[0034] Step 1: Preparation of processing aids:
[0035] S1: First, 6.5 parts of carbon nanotubes were sintered at 500°C for 10 hours, then placed in pure water to wash away surface impurities, acidified with 65% concentrated nitric acid for 6 hours, added to a mixed solution of 8 parts of ethanol and 5 parts of tetraethyl titanate at room temperature, heated to 50°C in a water bath, stirred for 2 hours, added with 5 parts of nitric acid, reacted in a water bath at 85°C for 8 hours, then added with 90 parts of pure water and cooled to room temperature to obtain a titanium dioxide / carbon nanotube solution;
[0036] S2: 7 parts of tetraethyl orthosilicate, 19 parts of ethanol, 0.9 parts of nitric acid and 0.5 parts of pure water were fully mixed and stirred to obtain a mixed solution A; 0.4 parts of ethanol were added to 0.6 parts of nitric acid solution to obtain a mixed solution B; 4 parts of the mixed solution B were added to 20 parts of the mixed solution A, heated in a water bath at 65°C with stirring, and reacted for 3 hours to obtain a silicon dioxide solution;
[0037] S3: 26 parts of titanium dioxide / carbon nanotube solution and 17 parts of silicon dioxide solution were mixed and stirred for 30 minutes, and a mixed solution of 2 parts of ethanol, 2 parts of diacetone alcohol and 1 part of N,N-dimethylformamide was added and stirred for 30 minutes, and then a mixed solution of 2 parts of ethanol, 1.8 parts of ethylene glycol methyl ether and 2 parts of N,N-dimethylformamide was added and stirred for 90 minutes to obtain a mixed solution C; the mixed solution C was dried at 100° C. to obtain a processing aid;
[0038] Step 2: 140 parts of fluororubber raw rubber, 25 parts of processing aid, 5 parts of antioxidant 1010, 1 part of palm wax, and 1 part of 4-bromophenol are added to an internal mixer, the materials are fully mixed at a temperature of 180°C, and then extruded, stretched, and pelletized through a twin-screw extruder at 160°C to obtain a raw rubber compound;
[0039] Step 3: A two-stage vulcanization method is used to add 0.5 parts of 2,4-dichlorobenzoyl peroxide and 120 parts of raw rubber mixed rubber into an internal mixer and disperse them evenly, and then a finished product is obtained through a hot pressing process. The first-stage vulcanization conditions are: pressure 10MPa, temperature 170°C, time 15min; the second-stage vulcanization conditions are: temperature 210°C, time 2h; during the molding process, the temperature is controlled at 240°C, the pressure is 3Mpa, and the molding time is 0.5h.
[0040] Embodiment 3:
[0041] Step 1: Preparation of processing aids:
[0042] S1: First, 5 parts of carbon nanotubes were sintered at 500°C for 10 hours, then placed in pure water to wash away surface impurities, acidified with 65% concentrated nitric acid for 6 hours, added to a mixed solution of 9 parts of ethanol and 4 parts of tetraethyl titanate at room temperature, heated to 50°C in a water bath, stirred for 2 hours, added with 4.4 parts of nitric acid, reacted in a water bath at 80°C for 8 hours, then added with 95 parts of pure water and cooled to room temperature to obtain a titanium dioxide / carbon nanotube solution;
[0043] S2: 7 parts of tetraethyl orthosilicate, 18 parts of ethanol, 0.8 parts of nitric acid and 0.6 parts of pure water were fully mixed and stirred to obtain a mixed solution A; 0.46 parts of ethanol were added to 0.75 parts of nitric acid solution to obtain a mixed solution B; 4 parts of the mixed solution B were added to 21 parts of the mixed solution A, heated in a water bath at 60°C with stirring, and reacted for 5 hours to obtain a silicon dioxide solution;
[0044] S3: 26 parts of titanium dioxide / carbon nanotube solution and 18 parts of silicon dioxide solution were mixed and stirred for 30 minutes, and a mixed solution of 2 parts of ethanol, 2 parts of diacetone alcohol and 1 part of N,N-dimethylformamide was added and stirred for 30 minutes, and then a mixed solution of 2 parts of ethanol, 1.8 parts of ethylene glycol methyl ether and 2 parts of N,N-dimethylformamide was added and stirred for 90 minutes to obtain a mixed solution C; the mixed solution C was dried at 100° C. to obtain a processing aid;
[0045] Step 2: 130 parts of fluororubber raw rubber, 26 parts of processing aid, 4 parts of antioxidant 1010, 2 parts of palm wax, and 3 parts of 4-bromophenol are fully mixed at a temperature of 160°C, and then extruded, stretched, and pelletized through a twin-screw extruder at 170°C to obtain a raw rubber compound;
[0046] Step 3: Use a two-stage vulcanization method to add 1.4 parts of 2,4-dichlorobenzoyl peroxide and 120 parts of raw rubber mixed rubber into an internal mixer and disperse them evenly, and then undergo a hot pressing process to obtain a finished product. The first-stage vulcanization conditions are: pressure 9.8MPa, temperature 165°C, time 12min; the second-stage vulcanization conditions are: temperature 200°C, time 3h; during the molding process, the temperature is controlled at 170°C, the pressure is 1.5Mpa, and the molding time is 1.5h.
[0047] Embodiment 4:
[0048] Step 1: Preparation of processing aids:
[0049] S1: First, 8 parts of carbon nanotubes were sintered at 500°C for 10 hours, then placed in pure water to wash away surface impurities, acidified with 65% concentrated nitric acid for 6 hours, added to a mixed solution of 9 parts of ethanol and 4 parts of tetraethyl titanate at room temperature, heated to 50°C in a water bath, stirred for 2 hours, added with 5 parts of nitric acid, reacted in a water bath at 85°C for 8 hours, and then added with 100 parts of pure water to cool to room temperature to obtain a titanium dioxide / carbon nanotube solution;
[0050] S2: 8 parts of tetraethyl orthosilicate, 15 parts of ethanol, 0.9 parts of nitric acid and 0.6 parts of pure water were fully mixed and stirred to obtain a mixed solution A; 0.4 parts of ethanol were added to 0.5 parts of nitric acid solution to obtain a mixed solution B; 3 parts of the mixed solution B were added to 21 parts of the mixed solution A, heated in a water bath at 55°C with stirring, and reacted for 4 hours to obtain a silicon dioxide solution;
[0051] S3: 25 parts of titanium dioxide / carbon nanotube solution and 20 parts of silicon dioxide solution were mixed and stirred for 30 minutes, and a mixed solution of 2 parts of ethanol, 2 parts of diacetone alcohol and 1 part of N,N-dimethylformamide was added and stirred for 30 minutes, and then a mixed solution of 2 parts of ethanol, 1.8 parts of ethylene glycol methyl ether and 2 parts of N,N-dimethylformamide was added and stirred for 90 minutes to obtain a mixed solution C; the mixed solution C was dried at 100° C. to obtain a processing aid;
[0052] Step 2: 130 parts of fluororubber raw rubber, 15 parts of processing aid, 3 parts of antioxidant 1010, 2 parts of palm wax, and 2 parts of 4-bromophenol are added to an internal mixer, the materials are fully mixed at a temperature of 170°C, and then extruded, stretched, and pelletized through a twin-screw extruder at 170°C to obtain a raw rubber compound;
[0053] Step 3: A two-stage vulcanization method is used to add 0.8 parts of 2,4-dichlorobenzoyl peroxide and 110 parts of raw rubber mixed rubber into an internal mixer and disperse them evenly, and then a finished product is obtained through a hot pressing process. The first-stage vulcanization conditions are: pressure 10MPa, temperature 160°C, time 10min; the second-stage vulcanization conditions are: temperature 210°C, time 2h; during the molding process, the temperature is controlled at 150°C, the pressure is 1Mpa, and the molding time is 2h.
[0054] Comparative Example 1:
[0055] The fluororubber is directly prepared without adding processing aids.
[0056] Step 1: 120 parts of fluororubber raw rubber, 1 part of antioxidant 1010, 1 part of palm wax, and 2 parts of 4-bromophenol are added to an internal mixer, the materials are fully mixed at a temperature of 150°C, and then extruded, stretched, and pelletized through a twin-screw extruder at 160°C to obtain a raw rubber compound;
[0057] Step 2: Use a two-stage vulcanization method to add 0.5 parts of 2,4-dichlorobenzoyl peroxide and 120 parts of raw rubber mixed rubber into an internal mixer and disperse them evenly, and then undergo a hot pressing molding process to obtain a finished product. The first-stage vulcanization conditions are: pressure 9MPa, temperature 160°C, time 10min; the second-stage vulcanization conditions are: temperature 210°C, time 2h; during the molding process, the temperature is controlled at 150°C, the pressure is 1Mpa, and the molding time is 2h.
[0058] Comparative Example 2:
[0059] Fluororubber was prepared using titanium dioxide / carbon nanotube composites as processing aids.
[0060] Step 1: Preparation of processing aids:
[0061] S1: First, 6.5 parts of carbon nanotubes were sintered at 500°C for 10 hours, then placed in pure water to wash away surface impurities, acidified with 65% concentrated nitric acid for 6 hours, added to a mixed solution of 8 parts of ethanol and 5 parts of tetraethyl titanate at room temperature, heated to 50°C in a water bath, stirred for 2 hours, added with 5 parts of nitric acid, reacted in a water bath at 85°C for 8 hours, then added with 90 parts of pure water and cooled to room temperature to obtain a titanium dioxide / carbon nanotube solution; dried at 100°C to obtain a processing aid;
[0062] Step 2: 140 parts of fluororubber raw rubber, 25 parts of processing aid, 5 parts of antioxidant 1010, 1 part of palm wax, and 1 part of 4-bromophenol are added to an internal mixer, the materials are fully mixed at a temperature of 180°C, and then extruded, stretched, and pelletized through a twin-screw extruder at 160°C to obtain a raw rubber compound;
[0063] Step 3: A two-stage vulcanization method is used to add 0.5 parts of 2,4-dichlorobenzoyl peroxide and 120 parts of raw rubber mixed rubber into an internal mixer and disperse them evenly, and then a finished product is obtained through a hot pressing process. The first-stage vulcanization conditions are: pressure 10MPa, temperature 170°C, time 15min; the second-stage vulcanization conditions are: temperature 210°C, time 2h; during the molding process, the temperature is controlled at 240°C, the pressure is 3Mpa, and the molding time is 0.5h.
[0064] Comparative Example 3:
[0065] Fluororubber was prepared using silica / carbon nanotube composites as processing aids.
[0066] Step 1: Preparation of processing aids:
[0067] First, 5 parts of carbon nanotubes were sintered at 500°C for 10 hours, then placed in pure water to wash away surface impurities, acidified with 65% concentrated nitric acid for 6 hours, added to a mixed solution of 28 parts of ethanol and 7 parts of tetraethyl titanate at room temperature, heated to 50°C in a water bath, stirred for 2 hours, added with 0.8 parts of nitric acid, reacted in a water bath at 80°C for 8 hours, then added with 95 parts of pure water and cooled to room temperature to obtain a silicon dioxide / carbon nanotube solution; dried at 100°C to obtain a processing aid;
[0068] Step 2: 130 parts of fluororubber raw rubber, 26 parts of processing aid, 4 parts of antioxidant 1010, 2 parts of palm wax, and 3 parts of 4-bromophenol are fully mixed at a temperature of 160°C, and then extruded, stretched, and pelletized through a twin-screw extruder at 170°C to obtain a raw rubber compound;
[0069] Step 3: Use a two-stage vulcanization method to add 1.4 parts of 2,4-dichlorobenzoyl peroxide and 120 parts of raw rubber mixed rubber into an internal mixer and disperse them evenly, and then undergo a hot pressing process to obtain a finished product. The first-stage vulcanization conditions are: pressure 9.8MPa, temperature 165°C, time 12min; the second-stage vulcanization conditions are: temperature 200°C, time 3h; during the molding process, the temperature is controlled at 170°C, the pressure is 1.5Mpa, and the molding time is 1.5h.
[0070] Comparative Example 4:
[0071] Carbon nanotubes, titanium dioxide and silicon dioxide powders were directly added as processing aids.
[0072] Step 1: 130 parts of fluororubber raw rubber, 3 parts of carbon nanotubes, 4 parts of titanium dioxide, 4 parts of silicon dioxide, 3 parts of antioxidant 1010, 2 parts of palm wax, and 2 parts of 4-bromophenol are added into an internal mixer, the materials are fully mixed at a temperature of 170° C., and then extruded, stretched, and pelletized through a twin-screw extruder at 170° C. to obtain a raw rubber compound;
[0073] Step 2: Use a two-stage vulcanization method to add 0.8 parts of 2,4-dichlorobenzoyl peroxide and 110 parts of raw rubber mixed rubber into an internal mixer and disperse them evenly, and then undergo a hot pressing molding process to obtain a finished product. The first-stage vulcanization conditions are: pressure 10MPa, temperature 160°C, time 10min; the second-stage vulcanization conditions are: temperature 210°C, time 2h; during the molding process, the temperature is controlled at 150°C, the pressure is 1Mpa, and the molding time is 2h.
[0074] Experiment: The silicone seals prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were tested for relevant properties, and the results are shown in the following table.
[0075] The tensile properties of the products without aging treatment, the products subjected to heat aging treatment at 180°C for 48 hours, and the products subjected to UV light for 100 hours were tested using a HY-5080 universal tensile testing machine in accordance with GB / T528-2009.
[0076] A fluororubber product with a diameter of 5 cm was selected and placed in a Candida albicans culture dish at 30°C. The colony count was tested after 48 hours and the antibacterial rate was calculated.
[0077]
[0078]
[0079] Conclusion: As shown in the table, the data of Examples 1 to 4 show that the fluororubber prepared by using the silica / titanium dioxide / carbon nanotube composite material as a processing aid has excellent performance. Among them, carbon nanotubes can improve the mechanical strength of fluororubber. Since carbon nanotubes have a very strong surface effect, they are prone to agglomeration, resulting in uneven synthetic rubber and affecting the quality. A layer of silica is prepared on the surface of carbon nanotubes by the sol-gel method, which can not only improve the strength of fluororubber, but also avoid agglomeration of carbon nanotubes. In addition, titanium dioxide can not only improve the strength of fluororubber and its antibacterial and anti-ultraviolet aging effects, but also improve the heat resistance of fluororubber as a metal oxide, and extend the storage time and service life of fluororubber. Taking Example 1 as the reference group, the data of Comparative Example 1 show that without adding processing aids, the various properties of fluororubber are poor; taking Example 2 as the reference group, the data of Comparative Example 2 show that the combination of silicon dioxide and carbon nanotubes has a synergistic effect on improving the strength of fluororubber; taking Example 3 as the reference group, the data of Comparative Example 3 show that titanium dioxide can significantly improve the antibacterial properties of fluororubber, and also enhance the heat aging resistance of fluororubber; taking Example 4 as the reference group, the data of Comparative Example 4 show that directly adding carbon nanotube powder leads to obvious agglomeration effect, the finished product is uneven, and various properties are reduced.
[0080] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an aging-resistant rubber material for a rubber-lined pipe, characterized in that: The following steps are involved: Step 1: S1: Treat the carbon nanotubes at 500°C and wash away the surface impurities, acidify with 65% concentrated nitric acid, add ethanol and titanate compound, heat to 50°C in a water bath, add nitric acid to react, cool with pure water, and obtain a titanium dioxide / carbon nanotube solution; S2: Mixing a silicate compound, ethanol, nitric acid and pure water to obtain a mixed solution A; Mixing ethanol and nitric acid to obtain a mixed solution B and adding the mixed solution B to the mixed solution A, heating the mixture for 3 to 5 hours to obtain a silicon dioxide solution; S3: mixing the titanium dioxide / carbon nanotube solution and the silicon dioxide solution, adding ethanol, diacetone alcohol, N,N-dimethylformamide, and ethylene glycol methyl ether, and reacting to obtain a mixed solution C; and drying to obtain a processing aid; In S2, the content of each component in the silicon dioxide solution is, by weight, 20 to 22 parts of mixed solution A and 2 to 4 parts of mixed solution B; the content of each component in the mixed solution A is, by weight: 6 to 8 parts of silicate compound, 15 to 20 parts of ethanol, 0.6 to 0.9 parts of nitric acid, and 0.5 to 1 parts of pure water; the content of each component in the mixed solution B is, by weight, 0.4 to 0.5 parts of ethanol and 0.5 to 0.8 parts of nitric acid; The content of each component in the processing aid described in S3 is calculated by weight: 25 to 28 parts of titanium dioxide / carbon nanotube solution, 15 to 20 parts of silicon dioxide solution, 4 parts of ethanol, 2 parts of diacetone alcohol, 3 parts of N,N-dimethylformamide, and 1.8 parts of ethylene glycol methyl ether; Step 2: mixing fluororubber raw rubber, processing aid, antioxidant, plasticizer and flame retardant at 150-180° C., extruding, drawing and pelletizing at 160-190° C. to obtain raw rubber mixed rubber; Step 3: adopt a two-stage vulcanization method, use a vulcanizing agent to vulcanize the raw rubber mix, and obtain the finished product through a hot pressing process.
2. The method for preparing an aging-resistant rubber material for a rubber-lined pipe according to claim 1, characterized in that: The content of each component in the raw rubber mixed rubber material in step 2 is, by weight, 120 to 150 parts of fluororubber raw rubber, 15 to 30 parts of processing aids, 1 to 5 parts of antioxidants, 1 to 3 parts of plasticizers, and 1 to 3 parts of flame retardants; in step 3, the content of each component is, by weight, 0.5 to 1.4 parts of vulcanizing agent and 100 to 120 parts of raw rubber mixed rubber material.
3. The method for preparing an aging-resistant rubber material for a rubber-lined pipe according to claim 1, characterized in that: The titanate compound in S1 is any one of tetraethyl titanate, tetraisopropyl titanate, and tetra-tert-butyl titanate; in S2, the silicate compound is any one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, isopropyl silicate, and butyl orthosilicate.
4. The method for preparing an aging-resistant rubber material for a rubber-lined pipe according to claim 1, characterized in that: The fluororubber raw rubber described in step 2 is any one of a copolymer of chloroethylene and trifluoroethylene, a copolymer of vinylidene fluoride and hexafluoropropylene, and a copolymer of vinylidene fluoride and trifluoroethylene; the antioxidant is one or more of 1010, 168, 1076, 626, and 1790; the plasticizer is one or more of dioctyl adipate, butyl epoxy oleate, dioctyl sebacate, propylene glycol adipate, polyisobutylene, and palm wax; the flame retardant is one or more of antimony trioxide, melamine cyanurate, 4-bromophenol, and pentabromodiphenyl ether; the vulcanizing agent described in step 3 is any one of benzoyl peroxide and 2,4-dichlorobenzoyl peroxide.
5. The method for preparing an aging-resistant rubber material for a rubber-lined pipe according to claim 1, characterized in that: In step 3, the first stage vulcanization conditions are: pressure 9-10MPa, temperature 160-170°C, time 10-15min; the second stage vulcanization conditions are: temperature 190-210°C, time 2-4h; during the molding process, the temperature is controlled at 150-240°C, the pressure is 1-3Mpa, and the molding time is 0.5-2h.
6. An aging-resistant rubber material for rubber-lined pipes prepared according to the method for preparing an aging-resistant rubber material for rubber-lined pipes according to any one of claims 1 to 5.
Citation Information
Patent Citations
Tear-resistant fluoro-rubber mixed compound and preparation method thereof
CN105218986A
Preparation method of heat-conducting foam tape resistant to thermal-oxidative aging
CN109135600A